2011
DOI: 10.1159/000331280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes between ‘On-Flap’ and ‘Off-Flap’ Epi-LASIK for Myopia: A Meta-Analysis

Abstract: Objective: To examine possible differences in clinical outcomes between off-flap and on-flap epipolis laser in situ keratomileusis (epi-LASIK) for myopia. Methods: Pertinent studies were selected by extensive searches. A total of 9 studies reporting on a total of 958 eyes were included in the present meta-analysis. Statistical analysis was performed using RevMan 5.0 software. Results: There were no significant differences in the final refractive spherical equivalent (p = 0.38), manifest refractive spherical eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…16,17 However, no such advantages have been confirmed and, in fact, some have reported increased pain, delayed epithelial healing, and inferior early visual outcomes compared with flap-off techniques. [18][19][20] The flap-off variant of this technique was termed Epi-LASIK flap-off (Epi-LASIK FO). 8,18 The advantage of Epi-LASIK and Epi-LASIK FO is absence of alcohol-related toxicity and possibly faster time to healing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 However, no such advantages have been confirmed and, in fact, some have reported increased pain, delayed epithelial healing, and inferior early visual outcomes compared with flap-off techniques. [18][19][20] The flap-off variant of this technique was termed Epi-LASIK flap-off (Epi-LASIK FO). 8,18 The advantage of Epi-LASIK and Epi-LASIK FO is absence of alcohol-related toxicity and possibly faster time to healing.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20] The flap-off variant of this technique was termed Epi-LASIK flap-off (Epi-LASIK FO). 8,18 The advantage of Epi-LASIK and Epi-LASIK FO is absence of alcohol-related toxicity and possibly faster time to healing. 21 With the wide variety of procedures available today to treat mild to moderate myopic astigmatism, the question remains as to which technique is superior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis comparing epithelial flap 'off' versus 'on' after Epi-LASIK, 47 it was concluded that the two techniques had equal visual and refractive outcomes for the treatment of myopia. Off-flap Epi-LASIK had more rapid re-epithelialisation and visual recovery compared to on-flap Epi-LASIK.…”
Section: Laser Ablation Algorithmsmentioning
confidence: 99%
“…The patients were fitted with a -0.50 D bandage contact lens with base curve of 8.6, until the epithelium healed (3-7 days). 17,18,19 Postoperatively, a nonsteroidal anti-inflammatory drop, ketorolac 0.5% was used at the time of surgery and continued four times a day for the first 24 hours. A solution of dilute tetracaine in artificial tears was given for use on an as needed basis to mitigate ocular discomfort.…”
Section: Surgical Techniquesmentioning
confidence: 99%